The Wonder Bread summer : a novel - Blau, Jessica Anya (Harper Perennial, 2013)
It's 1983 in Berkeley, California. Twenty-year-old Allie Dodgson is a straitlaced college student working part-time at a dress shop to make ends meet. But when the shop turns out to be a front for a dangerous drug-dealing business, Allie finds herself on the Iam, speeding toward Los Angeles in her best friend's Prelude with a Wonder Bag full of cocaine riding shotgun and a hit man named Vice Versa on her tail.--From back cover.